2021
DOI: 10.1542/hpeds.2020-003517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Health Care and Hospital Worker SARS-CoV-2 IgG Antibody in a Pediatric Hospital

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We did not perform baseline anti-spike antibody tests prior to vaccination. However, we did perform baseline anti-nucleocapsid antibody testing as another aim of this study and reported previously that the infection rate was extremely low (1.3%) in a larger number of HCWs participating in early studies at our site [17]. Thus, any additive effect of previously infected individuals can be considered to have negligible impact to these results.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We did not perform baseline anti-spike antibody tests prior to vaccination. However, we did perform baseline anti-nucleocapsid antibody testing as another aim of this study and reported previously that the infection rate was extremely low (1.3%) in a larger number of HCWs participating in early studies at our site [17]. Thus, any additive effect of previously infected individuals can be considered to have negligible impact to these results.…”
Section: Discussionmentioning
confidence: 94%
“…This study was completed at an academic, tertiary care pediatric hospital in Seattle, WA, U.S. Data were collected from participants enrolled in a longitudinal SARS-CoV-2 IgG serology study over a 12-month period (May 2020-May 2021), as approved by the Seattle Children's Hospital Institutional Review Board. A description of the enrollment process and inclusion criteria was previously reported [17]. Briefly, employed HCWs, including physicians, nurses, pharmacists, administrative staff, social workers, mental health evaluators, security team members, child life specialists, and housekeepers, were recruited if they worked at least one shift in a clinical setting 14 days prior to enrollment, and were not experiencing any COVID-19 related symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…A larger study of 530 pHCWs at an urban children's hospital in the Seattle, Washington also detected a low anti-SARS-CoV-2 IgG prevalence of only 0.9% (May 4-June 2, 2020) early in the pandemic, which is more than 4-fold lower than that identified in the Atlanta cohort. However, 2.3% of participants working in the Seattle pediatric ED tested positive, whereas only 0.01% of non-ED personnel tested positive (Tokareva et al, 2021), supporting the premise of the pediatric ED as a likely higher-risk clinical location. Given that the first case of SARS-CoV-2 infection in the US was reported on January 21, 2020 just outside Seattle, Washington, Seattle Children's Hospital activated a hospital incident command structure on January 22 in response to the first US case occurring regionally.…”
Section: Discussionmentioning
confidence: 88%
“…Reports of positivity in HCW cohorts early in the pandemic range widely from 37% in a highly affected area in Spain (Pérez-García et al, 2020) to just 1% positivity in a California community with low COVID-19 levels (Brant-Zawadzki et al, 2020). Few studies have evaluated the prevalence of SARS-CoV-2 infection in HCWs working primarily in facilities dedicated to pediatrics (pHCW) (Insúa et al, 2020;Tokareva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%